Effect of Mineral N on C and N Dynamics of Rice and Wheat Residues under Different Moisture Levels: Minerals in Rice and Wheat Growth - Ali, ljaz; Nabi, Ghulam (Biological Sciences - PJSIR, 2020)
Crop residue mineralization affects soil carbon (C) and nitrogen (N) dynamics during crop residue management in crop production. C and N mineralization dynamics of rice and wheat residues incorporated with and without mineral N under two moisture conditions were evaluated under laboratory conditions. Mineral N was applied @ 0.015 g/Kg (»30 Kg/ha), whereas soil moisture was maintained at high (» ? 15 KPa, near field capacity) and at low (» ? 500 KPa)moisture levels during course of study. Periodic determinations on CO2 ? C and N mineralized were performed over a period of 120 days. The highest peaks for CO2 ? C occurred during first week of the study which then reduced gradually until it attained an equilibrium. High moisture level enhanced CO2 ? C flux by 14% than low moisture level. Combined application of crop residues and mineral N released 17% more CO2 ? C than crop residue treatments without mineral N.In residue applied treatments, immobilization was 40% higher at high moisture level than that at low moisture level. Application of rice and wheat residues in combination with mineral N caused both immobilizations followed by mineralization phases at both moisture levels. At high moisture level, maximum immobilization occurred during initial 15 days, while at low moisture level it continued till about 30 days. After day15, mineralization started which continued to increase during remaining period of study at high moisture and at low moisture mineralization initiated from day 60 onward. Mineralization in rice residue was faster than that in wheat residues. Immobilization of N continued progressively in residue alone treated soils at both moisture levels during study period. In residue treated soils, increase in soil moisture increased soil organic carbon (SOC) and soil water stable aggregates (WSA) significantly by 14% and 55% over control respectively.Combined application of crop residues and mineral N increased SOC by 43% and WSA by 59%. This study indicated that incorporation of crop residues along with addition of mineral N in the presence of optimum moisture promoted its faster decomposition with a quicker mineral N release, more organic matter build up and soil structure improvement than crop residues incorporated without mineral N.